Video killed the radios star? Online music videos and recorded music sales - Kretschmer, Tobias (2021)
We study the heterogeneous effects of online video platforms on the sales volume and sales distribution of recorded music. Identification comes from two natural experiments in Germany. In 2009, virtually all music videos were blocked from YouTube as a result of a legal dispute. In 2013, the dedicated platform Vevo entered the market, making videos of a large number of artists available overnight. Our estimates suggest that restricting (enabling) access to online videos decreases (increases) recorded music sales on average by about 5%-10%. We show that the effect operates independently of the nature of video content, suggesting that user-generated content is as effective as official content. Moreover, we highlight heterogeneity in this effect: online music videos disproportionally benefit sales of new artists and sales of mainstream music.